1999
DOI: 10.1029/1999jb900065
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a phase change at the base of the mantle consistent with seismological observations

Abstract: Abstract. The phase change model for the origin of the D" seismic discontinuity is tested by comparing the results of convection modeling with seismic observations. We compute a number of global dynamic models that incorporate a phase change at the base of the mantle with different characteristics and transform the resulting temperature field and the distribution of phases to seismic velocities. Over 900 two-dimensional synthetic waveforms are computed for each of the models from which $, $cS, and $cd phases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
46
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 47 publications
9
46
0
Order By: Relevance
“…A deep phase transition has been considered in only one Earth-related modeling study [Sidorin et al, 1999], which focused on the seismic signature associated with such a phase transition, and concluded that it offered the best explanation of observed seismic structures such as the ''Lay discontinuity'', but did not investigate the dynamical effects of such a transition. The only studies on the dynamical effects of deep phase transitions were modeling Mars, which, due to its smaller size and lower gravity, has the equivalent of Earth's transition zone in its' deep mantle.…”
Section: Introductionmentioning
confidence: 99%
“…A deep phase transition has been considered in only one Earth-related modeling study [Sidorin et al, 1999], which focused on the seismic signature associated with such a phase transition, and concluded that it offered the best explanation of observed seismic structures such as the ''Lay discontinuity'', but did not investigate the dynamical effects of such a transition. The only studies on the dynamical effects of deep phase transitions were modeling Mars, which, due to its smaller size and lower gravity, has the equivalent of Earth's transition zone in its' deep mantle.…”
Section: Introductionmentioning
confidence: 99%
“…2,4 This transition to a post-perovskite phase answered questions related to the formation of the DЉ layer and offered reasonable explanations to most seismic observations. [4][5][6][7][8] The experimental difficulties related to obtaining the postperovskite phase in MgSiO 3 , due to the large transition pressures and temperatures and to the transparency of the pure material to laser, determined scientists to search for analogous materials, where a similar phase transition sequence is observed, but at lower pressures and/or temperatures. These analogous materials ideally present similar physical properties as the phase of interest, and are more easily observed.…”
Section: Introductionmentioning
confidence: 99%
“…Equations (6) and (7) are discretised by finite elements with linear basis functions and solved simultaneously (modified after Ramage and Walthan, 1992) using a multigrid method. The energy equation is discretised by the MPDAT algorithm (Smolarkiewicz, 1984) and integrated with a Runge-Kutta scheme using explicit time stepping. Domain decomposition is used for the parallelisation (Bunge & Baumgardner, 1995) with MPI.…”
Section: Numericsmentioning
confidence: 99%
“…The existence of geochemically distinct reservoirs in the Earth's mantle is inferred from the observation of worldwide rather homogeneous mid-ocean ridge basalts (MORB) on the one hand and heterogeneous ocean island basalts (OIB) on the other (Zindler and Hart, 1986, Silver et al, 1988, Hart and Zindler, 1989, Allègre and Lewin, 1995, Hofmann, 1997. Of course, what we observe today is the result of the interplay between chemical differentiation and convective stirring that started with the formation of the Earth and is still going on.…”
Section: Introductionmentioning
confidence: 99%